Chrysophanol-8-O-glucoside protects mice against acute liver injury by inhibiting autophagy in hepatic stellate cells and inflammatory response in liver-resident macrophages - Wang, Tao; Lu, Zhuo; Qu, Xin-Hui; Xiong, Zi-Ying; Wu, Ya-Ting; Luo, Yong; Zhang, Zi-Yu; Han, Xiao-Jian; Xie, Cai-Feng (Frontiers in Pharmacology, 2022)
Acute liver failure (ALF) is an unfavorable condition characterized by the rapid loss of liver function and high mortality. Chrysophanol-8-O-glucoside (CPOG) is an anthraquinone derivative isolated from rhubarb. This study aims to evaluate the protective effect of CPOG on lipopolysaccharide (LPS)/D-GalN-induced ALF and its underlying mechanisms. LPS/D-GalN-induced mice ALF model and LPS treatment model in RAW 264.7 and LX2 cells were established. It was found that CPOG ameliorated LPS/D-GalN-induced liver injury and improved mortality as indicated by Hematoxylin-eosin (H&E) staining. Molecularly, qPCR and ELISA results showed that CPOG alleviated LPS/D-GalN-induced release of alanine aminotransferase and aspartate transaminase and the secretion of TNF-α and IL-1β in vivo. LPS/D-GalN-induced intracellular ROS production was also attenuated by CPOG in liver tissue. Further, CPOG attenuated ROS generation and inhibited the expression of p-IκB and p-p65 as well as the expression of TNF-α and IL-1β stimulated by LPS in RAW 264.7 cells. In addition, CPOG alleviated LPS-induced up-regulation of LC3B, p62, ATG5 and Beclin1 by attenuating ROS production and inhibiting MAPK signaling in LX2 cells. Taken together, our data indicated that the CPOG protected against LPS/D-GalN-induced ALF by inhibiting oxidative stress, inflammation response and autophagy. These findings suggest that CPOG could be potential drug for the treatment of ALF in clinic.